Evaluation of effectiveness of intermittent inhalational entonox in comparison with opioid tramadol for labour analgesia - Kumar, Amit; Chandel, Y. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Childbirth is an emotion-filled event and the mother needs to bond with her newborn baby as early as possible. Any intervention that leads to improvement in pain relief is worthy of investigation. Entonox, opioids as well as epidural analgesia are effective means for pain relief in labour, notwithstanding their shortcomings. The objectives of study are to compare the effectiveness of intermittent inhalational Entonox for labour analgesia with intramuscular opioid (Tramadol) and to compare the effects of Entonox and Tramadol as labour analgesia on the maternal and fetal outcome of labour. Methods: The study was a prospective randomized, comparative study of two established techniques of labour analgesia. The study was carried out in 100 subjects. These subjects are divided into two groups. Group A - Tramadol Group: 50 women in active labour who received 100 mg tramadol intramuscularly with repeat dose of 50mg tramadol 4 hourly. Group B - Entonox Group: 50 women in active labour who received entonox for labour analgesia. Results: The mean VAS (visual analogue score) i.e. the pain score in group I (Tramadol) was 4.58±1.54 and Group II (Entonox) was 4.02±1.99 which is significantly low when compared to Group I (Tramadol) p<0.001. Study also showed that both the analgesics Entonox as well as Tramadol does not cause any significant change when compared for duration of labor. The rate of instrumental assisted vaginal deliveries and normal vaginal deliveries were almost equal in both the groups. In our study, the mean overall satisfaction level of the parturients in group II (Entonox) at 1 hr post delivery was (5.06±1.42) and 24 hr post delivery was (6.64±1.66) which was more when compared with tramadol group. The difference was statistically significant (p value was <0.001). This indicates that overall satisfaction level of the parturients is more with the use of Entonox when compared with Tramadol. Conclusions: Therefore, it is concluded that intermittent inhalational Entonox provides better labour analgesia then intramuscular opioid Tramadol.